Longitudinal anemia status and risk for adverse outcomes in former smokers with COPD - Yukiko Kunitomo; Han Woo; Aparna Balasubramanian; Ashraf Fawzy; Cheng Ting Lin; Sarath Raju; Daniel C Belz; Meredith C McCormack; Kirsten Koehler; Nadia N Hansel; Nirupama Putcha (Respiratory Research)
Abstract Background Anemia is a prevalent comorbidity in COPD associated with increased morbidity. However, the significance of longitudinal anemia status and variation in anemia status trends over time in COPD are not known. Furthermore, individuals with COPD and smoking history often have multiple comorbidities, in particular cardiovascular disease. The objective of this study was to evaluate the association between longitudinal anemia status and COPD outcomes, accounting for comorbid cardiovascular disease. Methods Serial hemoglobin measures and clinical outcomes were obtained in former smokers with moderate to severe COPD from two clinical studies over a 6-to-9-month period. In the first analysis, the association between repeated measures of time-varying anemia status and outcomes was assessed by generalized estimating equations adjusted for covariates including cardiovascular disease. In the second analysis, each participant’s anemia risk profile during the study period was characterized as high versus low anemia risk-growth rate. Mean differences in the progression of COPD outcomes over time between the two groups were assessed using a generalized linear mixed model. Effect modification by baseline coronary artery calcium (CAC) burden was explored. Results There were 159 individuals with mean age of 66.5 years (± 8.3) and mean FEV1% predicted of 51.4% (± 17.0), of which 41% were ever-anemic during the study period. Repeated measures of anemia status were associated with higher St. George’s Respiratory Questionnaire (SGRQ) scores (β 2.5, 95% CI: 0.1,4.8, p = 0.04), lower 6-minute walk distance (6MWD) (β -38.6, 95% CI: -67.7,-7.4, p = 0.02), and higher rate of moderate-to-severe exacerbations over the prospective follow-up period (IRR 1.8, 95% CI: 1.1,2.8, p = 0.02). There was effect modification by CAC burden such that with higher burden the mean difference in COPD outcome by anemia status was greater for a subset of symptom scores. Participants with profiles of increasing anemia risk had higher estimated rates of decline in the FEV1% predicted and 6MWD and increase in SGRQ scores compared to those with stable or decreasing anemia risk. Conclusions Longitudinal anemia status trends may be predictive of COPD disease trajectory. Anemia status by repeated measures analysis is associated with COPD morbidity with potentially stronger associations in the setting of high CAC burden.